Method for improving the first coulomb efficiency of a porous carbon-based silicon-carbon composite negative electrode material

CN122992006APending Publication Date: 2026-10-27BAOWU CHARCOAL MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510521952.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,这种方法并不适用于硅碳复合负极,因为硅碳复合负极与氢化锂在低于800摄氏度时反应不完全,残留的氢化锂在接触空气时会产生杂质,从而影响最终产品的性能

Benefits of technology

[0030]本发明针对多孔碳基的硅碳复合负极材料,补锂过程中采用液氮、氨气利用氨的低温冷凝毛细作用将锂单质粉体携带进入多孔碳内部,锂单质和硅形成硅锂合金完成补锂反应,完成硅碳复合负极材料的预锂化,提高硅碳复合负极材料首次库伦效率。本发明获得的硅碳复合负极材料首次库伦效率≥93%,达到与广泛使用的石墨材料同等水平。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992006A_ABST
    Figure CN122992006A_ABST
Patent Text Reader

Abstract

The application discloses a method for improving the first coulomb efficiency of a porous carbon-based silicon-carbon composite negative electrode material, and is characterized in that, in view of the unique structure of the porous carbon-based material, liquid nitrogen, ammonia and lithium are used, and the low-temperature condensation capillary action of ammonia is utilized to carry lithium powder into the interior of the porous carbon, so that the lithium and silicon form a silicon-lithium alloy to complete a lithium supplement reaction, prelithiation of the silicon-carbon composite negative electrode material is completed, and the first coulomb efficiency of the silicon-carbon composite negative electrode material is improved. In addition, no impurities are introduced, and the service life of the battery is prevented from being reduced due to the introduction of impurities. The first coulomb efficiency of the silicon-carbon composite negative electrode material obtained by the application is greater than or equal to 93%, and reaches the same level as that of widely used graphite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery anode material technology, specifically relating to a method for improving the first coulombic efficiency of porous carbon-based silicon-carbon composite anode materials. Background Technology

[0002] With the strong demand for high-performance lithium-ion batteries from the electric vehicle industry, the research and application of silicon-carbon composite materials as anode materials are receiving increasing attention. This material, composed of silicon and carbon, has a theoretical capacity more than three times that of traditional carbon-based anode materials, and is gradually becoming a new favorite in the lithium-ion battery anode material market.

[0003] Nevertheless, silicon-carbon composite anodes face some challenges in practical applications. Their initial coulombic efficiency is relatively low (90% for silicon-carbon composite anodes and 94% for graphite anodes), and their electronic conductivity is also unsatisfactory. Initial coulombic efficiency refers to the ratio of discharge capacity to charge capacity during the first charge and discharge cycle of a battery. Low efficiency leads to a reduction in the battery's actual usable energy density and may cause irreversible lithium loss from the cathode material.

[0004] Studies have shown that the low initial coulombic efficiency of silicon-carbon composite anodes is mainly attributed to the irreversible deposition of lithium ions at the material interface and pores during the initial insertion process, as well as the formation of a solid electrolyte interphase (SEI) film.

[0005] To overcome these problems, researchers are looking for solutions from silicon oxide materials.

[0006] Chinese patent CN102214823A discloses a method for depositing a carbon layer on the surface of silicon oxide using chemical vapor deposition (CVD) technology, followed by calcination with lithium hydride. However, this method is not suitable for silicon-carbon composite anodes because the reaction between silicon-carbon composite anodes and lithium hydride is incomplete below 800 degrees Celsius, and the residual lithium hydride will generate impurities when exposed to air, thus affecting the performance of the final product.

[0007] Chinese patent CN102916164A discloses a method for replenishing lithium to the positive electrode of a lithium-ion battery. The method involves dissolving lithium in an organic solvent to replenish the positive electrode material and the silicon-carbon negative electrode. However, since the silicon-carbon negative electrode material is based on porous carbon, it has a porous structure and abundant interfaces. When using an organic lithium solution for replenishment, the organic solvent that has permeated the material is difficult to completely remove in subsequent steps. This results in the organic solvent remaining inside the negative electrode material, causing the negative electrode material to generate gas and damaging the battery. Summary of the Invention

[0008] The purpose of this invention is to provide a method for improving the initial coulombic efficiency of porous carbon-based silicon-carbon composite anode materials. This method pre-lithiates the porous carbon-based material without introducing impurities, thereby improving the initial coulombic efficiency of the silicon-carbon composite anode material. The silicon-carbon composite anode material obtained by this invention has an initial coulombic efficiency of ≥93%, reaching the same level as widely used graphite materials, and the gas production value is ≤0.15mL / g, avoiding the impact of impurities on the increased gas production value and battery life.

[0009] To achieve the above objectives, the technical solution of the present invention is as follows:

[0010] A method for improving the first coulombic efficiency of porous carbon-based silicon-carbon composite anode materials includes the following steps:

[0011] 1) The porous carbon material is placed in a reaction apparatus, and an inert gas is introduced into the apparatus to replace the air. Then, the temperature is raised to 500–1000°C, and a silicon source gas is introduced into the apparatus to obtain a silicon-carbon precursor. The porous carbon material has a specific surface area of ​​500–3000 m². 2 / g, wherein the mass ratio of the porous carbon material to the silicon source gas is 1:10 to 10:1;

[0012] 2) A carbon-containing gas is introduced into the reaction apparatus to perform preliminary surface carbon coating on the silicon-carbon precursor, thereby obtaining a carbon-coated silicon-carbon precursor. The reaction temperature is 600-1000℃, and the amount of carbon-containing gas introduced is 1-20% of the total mass of the porous carbon material.

[0013] 3) The carbon-coated silicon carbide precursor is mixed evenly with lithium elemental powder and placed in a sealed container filled with nitrogen. Liquid nitrogen is then injected, followed by ammonia gas. After the reaction is completed, a lithiated carbon-coated silicon carbide precursor is obtained. The mass ratio of the carbon-coated silicon carbide precursor to the lithium elemental powder is 10 to 1000:1. The amount of liquid nitrogen added is 1 to 10 times the mass of the lithium elemental powder, and the mass of ammonia gas is 0.01 to 100 times the mass of the lithium elemental powder.

[0014] 4) The lithium-coated carbon-coated silicon-carbon precursor is placed in a reaction device, the temperature is controlled at 600-1000℃, and carbon-containing gas is introduced into the reaction device to complete the surface carbon coating and obtain silicon-carbon composite anode material. The amount of carbon-containing gas introduced is 1-20% of the total mass of the porous carbon material.

[0015] Preferably, in step 1), the porous carbon material is one or more of soft carbon, hard carbon, biomass-derived carbon, resin-derived carbon, pitch-derived carbon, and graphitized carbon. More preferably, the porous carbon material is hard carbon.

[0016] Preferably, in step 1), the silicon source gas is one or more of silane, disilane, dichlorosilane, and trichlorosilane.

[0017] Preferably, in step 1), the reaction time after introducing silicon source gas into the reaction device is 10 minutes to 20 hours.

[0018] Preferably, the carbon-containing gas is a carbon-containing gas produced by the cracking of hydrocarbons, benzenes, and alcohols at 500–800°C.

[0019] Preferably, in step 2), the reaction time is ≥5 min.

[0020] Preferably, in step 3), the reaction time after the ammonia gas is introduced is 1 minute to 5 hours.

[0021] Preferably, in step 4), the surface carbon coating time is ≥30 min.

[0022] The silicon-carbon composite anode material obtained by this invention has a specific surface area ≤5m². 2 / g, initial coulombic efficiency ≥93%, gas production value ≤0.15mL / g.

[0023] The porous carbon material selected in this invention can be one or more of soft carbon, hard carbon, biomass-derived carbon, resin-derived carbon, pitch-derived carbon, and graphitized carbon. Preferably, hard carbon is selected as the porous carbon material to obtain better recycling performance.

[0024] Before the reaction begins, an inert gas is used to replace the air. The air in the pores of the porous carbon material needs to be completely replaced; otherwise, an oxidation side reaction will occur in subsequent steps, causing the silicon in the material to be converted into silicon oxide, which will reduce the initial coulombic efficiency of the anode material.

[0025] The purpose of using carbon-containing gas to perform preliminary surface carbon coating on the material is to reduce the specific surface area of ​​the silicon-carbon precursor. The specific surface area of ​​the carbon-coated silicon-carbon precursor obtained after preliminary surface carbon coating is ≤100m². 2 / g, to avoid excessive specific surface area adsorbing air and reacting, causing silicon in the material to transform into silicon oxide, affecting the bonding of silicon and lithium in the subsequent pre-lithiation process, and reducing the coulombic efficiency of the first anode material.

[0026] A carbon-coated silicon-carbon precursor is uniformly mixed with lithium powder and placed in a sealed container with liquid nitrogen added. Subsequent ammonia gas is introduced and liquefied at low temperature, causing more lithium powder to float to the surface. Due to the porous structure and abundant interfaces of the porous carbon material, liquid ammonia easily penetrates into the porous carbon interior through capillary action. As the liquid ammonia enters the porous carbon, it carries the lithium powder in. The liquid ammonia and lithium form chemical bonds and separate into ammonia gas and lithium upon ammonia vaporization. The ammonia gas carries the lithium into the silicon crystals within the porous carbon, where it forms a silicon-lithium alloy, completing the lithium replenishment reaction. This reaction provides more additional lithium to the silicon-carbon composite anode, compensating for lithium loss when used as an anode material in lithium-ion batteries, thus achieving an initial improvement in coulombic efficiency. Simultaneously, the liquid nitrogen, ammonia molecules, and residual ammonia on the material surface volatilize during subsequent reactions, leaving no residue on the anode material surface and avoiding the impact of other impurities on the anode material's performance.

[0027] The pre-lithiation process should be carried out under an inert atmosphere to avoid side reactions between metallic lithium and water, oxygen, carbon dioxide, etc. in the air, which would affect the bonding between silicon carbide materials and lithium.

[0028] The reaction time for surface carbon coating of the lithiated carbon-coated silicon-carbon precursor should be greater than 30 minutes to ensure complete evaporation of residual lithium-containing solvent and diffusion and migration of lithium into the material interior, and to ensure that the specific surface area of ​​the surface-coated silicon-carbon composite anode is ≤5m². 2 / g, so that silicon and lithium in the pores of the negative electrode material are completely encapsulated and do not come into direct contact with the external environment, thus avoiding lithium loss and the reduction of the first coulombic efficiency of the negative electrode material.

[0029] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0030] This invention targets porous carbon-based silicon-carbon composite anode materials. During the lithium replenishment process, liquid nitrogen and ammonia are used. The low-temperature condensation and capillary action of ammonia carry elemental lithium powder into the porous carbon interior. The elemental lithium and silicon form a silicon-lithium alloy, completing the lithium replenishment reaction and pre-lithiation of the silicon-carbon composite anode material, thus improving its initial coulombic efficiency. The silicon-carbon composite anode material obtained by this invention achieves an initial coulombic efficiency ≥93%, reaching the same level as widely used graphite materials.

[0031] The liquid nitrogen and ammonia used in the pre-lithiation method of this invention will directly evaporate in subsequent processes and will not remain on the material. However, when using traditional organic solvents as solvents for lithium replenishment, the porous structure and abundant interfaces of the porous carbon material make it difficult for the organic solvent to be completely removed in subsequent steps. This leads to the residue of organic solvent inside the anode material, resulting in many impurities in the final silicon-carbon composite anode material. Batteries made with silicon-carbon composite anode materials containing impurities will produce gas during use, thereby damaging the battery and reducing its lifespan. The silicon-carbon composite anode material obtained by this invention has a gas production value ≤0.15mL / g, avoiding the impact of impurities on the increased gas production value and battery life. Attached Figure Description

[0032] Figure 1 The image shows the XRD pattern of the silicon-carbon composite anode material obtained in Example 1 of this invention.

[0033] Figure 2 The first charge-discharge curve of the silicon-carbon composite anode material obtained in Example 1 of this invention is shown. Detailed Implementation

[0034] The present invention will be further described below with reference to the embodiments and accompanying drawings.

[0035] Example 1

[0036] A method for improving the first coulombic efficiency of porous carbon-based silicon-carbon composite anode materials includes the following steps:

[0037] 1) To prepare porous carbon materials, the porous carbon materials were placed in a reaction apparatus, and an inert gas was introduced into the reaction apparatus to replace the air. Then the temperature was raised to 500°C, and silane gas was introduced into the reaction apparatus. The total mass ratio of silane gas to porous carbon materials was 1.4:1. The reaction was carried out for 1 hour to obtain silicon-carbon precursors.

[0038] 2) Then, carbon-containing gas is introduced into the reaction device. The amount of carbon-containing gas added is 10% of the mass of the silicon-carbon precursor. The carbon-containing gas is a mixture of acetylene and propane in a volume ratio of 1:1. The temperature is raised to 600°C to perform preliminary surface carbon coating on the silicon-carbon precursor, thereby obtaining carbon-coated silicon-carbon precursor.

[0039] 3) Mix 500g of carbon-coated silicon carbide precursor with 14g of lithium elemental powder evenly, and place it in a sealed container filled with nitrogen. Then inject 50g of liquid nitrogen, followed by 500g of ammonia gas. Continue to introduce nitrogen gas to maintain positive pressure inside the container. After reacting for 1 hour, lithiated carbon-coated silicon carbide precursor is obtained.

[0040] 4) The lithium-coated carbon-coated silicon-carbon precursor is placed in a reaction apparatus and the temperature is controlled at 600℃. Carbon-containing gas is introduced into the reaction apparatus. The amount of carbon-containing gas added is 3% of the mass of the silicon-carbon precursor. The carbon-containing gas is a mixture of acetylene and propane in a volume ratio of 1:1. The surface carbon coating is completed after 1 hour of reaction, and silicon-carbon composite anode material is obtained.

[0041] Figure 1 The image shows the XRD pattern of the silicon-carbon composite anode material obtained in Example 1 of this invention. Figure 1 It can be seen that the lithiation-treated material does not show any lithium peaks or other impurity peaks, indicating that there is no lithium or impurity residue in the material.

[0042] Figure 2 The first charge-discharge curve of the silicon-carbon composite anode material obtained in Example 1 of this invention is shown below. Figure 2 As can be seen from the comparison of the charging curve and the discharging curve, the silicon-carbon composite anode material obtained in Example 1 has an initial coulombic efficiency of 93.7%.

[0043] Example 2

[0044] A method for improving the first coulombic efficiency of porous carbon-based silicon-carbon composite anode materials includes the following steps:

[0045] 1) To prepare porous carbon materials, the porous carbon materials were placed in a reaction apparatus, and an inert gas was introduced into the reaction apparatus to replace the air. Then the temperature was raised to 1000℃, and silane gas was introduced into the reaction apparatus. The total mass ratio of silane gas to porous carbon materials was 5:1. The reaction was carried out for 0.5h to obtain silicon-carbon precursors.

[0046] 2) Then, carbon-containing gas is introduced into the reaction device. The amount of carbon-containing gas added is 2% of the mass of the silicon-carbon precursor. The carbon-containing gas is a mixture of acetylene and propane in a volume ratio of 1:5. The temperature is controlled at 800℃ to perform preliminary surface carbon coating on the silicon-carbon precursor, thereby obtaining carbon-coated silicon-carbon precursor.

[0047] 3) Mix 1000g of carbon-coated silicon carbide precursor with 14g of lithium elemental powder evenly, and place it in a sealed container filled with nitrogen. Then inject 20g of liquid nitrogen, followed by 30g of ammonia gas. Continue to purge nitrogen gas to maintain positive pressure inside the container. After reacting for 10 minutes, lithiated carbon-coated silicon carbide precursor is obtained.

[0048] 4) The lithium-coated carbon-coated silicon-carbon precursor is placed in a reaction apparatus and the temperature is controlled at 600℃. Carbon-containing gas is introduced into the reaction apparatus. The amount of carbon-containing gas added is 20% of the mass of the silicon-carbon precursor. The carbon-containing gas is a mixture of acetylene and propane in a volume ratio of 1:5. The surface carbon coating is completed after 1 hour of reaction, and silicon-carbon composite anode material is obtained.

[0049] Example 3

[0050] A method for improving the first coulombic efficiency of porous carbon-based silicon-carbon composite anode materials includes the following steps:

[0051] 1) To prepare porous carbon materials, the porous carbon materials were placed in a reaction apparatus, and an inert gas was introduced into the reaction apparatus to replace the air. Then the temperature was raised to 800°C, and silane gas was introduced into the reaction apparatus. The total mass ratio of silane gas to porous carbon materials was 10:1. The reaction was carried out for 5 hours to obtain silicon-carbon precursors.

[0052] 2) Then, carbon-containing gas is introduced into the reaction device. The amount of carbon-containing gas added is 20% of the mass of the porous carbon material. The carbon-containing gas is a mixture of acetylene and propane in a volume ratio of 4:1. The temperature is controlled at 1000℃ to perform preliminary surface carbon coating on the silicon-carbon precursor, thereby obtaining a carbon-coated silicon-carbon precursor.

[0053] 3) Mix 1000g of carbon-coated silicon carbide precursor with 14g of lithium elemental powder evenly, and place it in a sealed container filled with nitrogen. Then inject 140g of liquid nitrogen, followed by 150g of ammonia gas. Continue to introduce nitrogen gas to maintain positive pressure inside the container. After reacting for 5 hours, lithiated carbon-coated silicon carbide precursor is obtained.

[0054] 4) The lithium-coated carbon-coated silicon-carbon precursor is placed in a reaction apparatus and the temperature is controlled at 600℃. Carbon-containing gas is introduced into the reaction apparatus. The amount of carbon-containing gas added is 11% of the mass of the porous carbon material. The carbon-containing gas is a mixture of acetylene and propane in a volume ratio of 4:1. The surface carbon coating is completed after 1 hour of reaction, and silicon-carbon composite anode material is obtained.

[0055] Comparative Example 1

[0056] The difference from Example 1 of the present invention is that step 3) pre-lithiation is not performed in its preparation method, while other conditions are the same as in Example 1 of the present invention.

[0057] Comparative Example 2

[0058] The difference from Example 1 of this invention lies in the preparation method. In step 3) pre-lithiation, the carbon-coated silicon-carbon precursor is immersed in a lithium-containing tetrahydrofuran solution and stirred for 30 minutes. The lithiated carbon-coated silicon-carbon precursor is then separated. The lithium-containing tetrahydrofuran solution is obtained by dissolving 14g of lithium in 2L of tetrahydrofuran. Other conditions are the same as in Example 1 of this invention.

[0059] The negative electrode material obtained in the embodiments and comparative examples of the present invention, 80 wt% of SP and 10 wt% of PVDF, were dispersed in NMP to form a uniform slurry, which was then coated on copper foil. After vacuum drying, it was stamped into a circular electrode sheet. Lithium metal was used as the counter electrode, 1 mol / L LiPF6 / DMC+DEC+EC (volume ratio of 1:1:1) was used as the electrolyte, and Celgard 2400 was used as the separator to form a test battery.

[0060] The battery was subjected to constant current charge-discharge tests with a charge-discharge voltage range of 0.01–1.5V. The initial coulombic efficiency of the material was measured, and the results are shown in Table 1.

[0061] The negative electrode material obtained in the embodiments and comparative examples of the present invention was dispersed in NMP at 80 wt% with SP and 10 wt% PVDF to form a uniform slurry, which was then coated on copper foil. After vacuum drying, it was stamped into a 5 cm * 4 cm square electrode sheet. The ternary positive electrode material was used as the counter electrode, 1 mol / L LiPF6 / DMC+DEC+EC (volume ratio of 1:1:1) was used as the electrolyte, and Celgard 2400 was used as the separator to form a test single-layer soft pack battery.

[0062] The battery was left to stand at 45°C for 60 hours. The volume change of the battery before and after standing was measured by the water displacement method, and the gas production value was calculated. The calculated gas production value is shown in Table 1.

[0063] Table 1

[0064]

[0065]

[0066] As can be seen from Table 1, the initial coulombic efficiency of the embodiments of the present invention is improved compared with that of Comparative Example 1, but the gas production value is comparable, proving that no impurity elements are introduced into the material after pre-lithiation.

[0067] Compared with Comparative Example 2, the embodiment of the present invention has a higher initial coulombic efficiency and a lower gas production value, which proves that the pre-lithiation effect of the material of the present invention is better than that of Comparative Example 2, and no new impurities are introduced that would increase the gas production value and affect the battery life.

Claims

1. A method for improving the first-pass coulombic efficiency of porous carbon-based silicon-carbon composite anode materials, characterized in that, Includes the following steps: 1) The porous carbon material is placed in a reaction apparatus, and an inert gas is introduced into the apparatus to replace the air. Then, the temperature is raised to 500–1000°C, and a silicon source gas is introduced into the apparatus to obtain a silicon-carbon precursor. The porous carbon material has a specific surface area of ​​500–3000 m². 2 / g, wherein the mass ratio of the porous carbon material to the silicon source gas is 1:10 to 10:1; 2) A carbon-containing gas is introduced into the reaction apparatus to perform preliminary surface carbon coating on the silicon-carbon precursor, thereby obtaining a carbon-coated silicon-carbon precursor. The reaction temperature is 600-1000℃, and the amount of carbon-containing gas introduced is 1-20% of the total mass of the porous carbon material. 3) The carbon-coated silicon carbide precursor is mixed evenly with lithium elemental powder and placed in a sealed container filled with nitrogen. Liquid nitrogen is then injected, followed by ammonia gas. After the reaction is completed, a lithiated carbon-coated silicon carbide precursor is obtained. The mass ratio of the carbon-coated silicon carbide precursor to the lithium elemental powder is 10 to 1000:

1. The amount of liquid nitrogen added is 1 to 10 times the mass of the lithium elemental powder, and the mass of ammonia gas is 0.01 to 100 times the mass of the lithium elemental powder. 4) The lithium-coated carbon-coated silicon-carbon precursor is placed in a reaction device, the temperature is controlled at 600-1000℃, and carbon-containing gas is introduced into the reaction device to complete the surface carbon coating and obtain silicon-carbon composite anode material. The amount of carbon-containing gas introduced is 1-20% of the total mass of the porous carbon material.

2. The method for improving the first coulombic efficiency of porous carbon-based silicon-carbon composite anode materials as described in claim 1, characterized in that, In step 1), the porous carbon material is one or more of soft carbon, hard carbon, biomass-derived carbon, resin-derived carbon, pitch-derived carbon, and graphitized carbon. Preferably, the porous carbon material is hard carbon.

3. The method for improving the first coulombic efficiency of porous carbon-based silicon-carbon composite anode materials as described in claim 1, characterized in that, In step 1), the silicon source gas is one or more of silane, silane, dichlorosilane, and trichlorosilane.

4. The method for improving the first coulombic efficiency of porous carbon-based silicon-carbon composite anode materials as described in claim 1, characterized in that, In step 1), the reaction time after introducing silicon source gas into the reaction device is 10 minutes to 20 hours.

5. The method for improving the first coulombic efficiency of porous carbon-based silicon-carbon composite anode materials as described in claim 1, characterized in that, The carbon-containing gas is produced by the cracking of hydrocarbons, benzenes, and alcohols at 500–800°C.

6. The method for improving the first coulombic efficiency of porous carbon-based silicon-carbon composite anode materials as described in claim 1, characterized in that, In step 2), the reaction time is ≥5 min.

7. The method for improving the first coulombic efficiency of porous carbon-based silicon-carbon composite anode materials as described in claim 1, characterized in that, In step 2), the obtained carbon-coated silicon-carbon precursor has a specific surface area ≤100m². 2 / g.

8. The method for improving the first coulombic efficiency of porous carbon-based silicon-carbon composite anode materials as described in claim 1, characterized in that, In step 3), the reaction time after ammonia gas is introduced is from 1 minute to 5 hours.

9. The method for improving the first coulombic efficiency of porous carbon-based silicon-carbon composite anode materials as described in claim 1, characterized in that, In step 4), the surface carbon coating time is ≥30 min.

10. The method for improving the first coulombic efficiency of porous carbon-based silicon-carbon composite anode materials as described in claim 1, characterized in that, In step 4), the obtained silicon-carbon composite anode material has a specific surface area ≤ 5 m². 2 / g, initial coulombic efficiency ≥93%, gas production value ≤0.15mL / g.

Citation Information

Patent Citations

  • Negative electrode material for secondary battery with non-aqueous electrolyte, method for manufacturing negative electrode material for secondary battery with non-aqueous electrolyte, and lithium ion secondary battery

    CN102214823A

  • Method for supplementing lithium to lithium-ion battery positive plate

    CN102916164A